Analysis of Marketing Performance of Batik Businesses in Pekalongan Through Entrepreneurial Orientation, Market Orientation, Product Innovation and E-Commerce - Siti Yunitarini; Moh. Mulya Falah; Alan Gustofa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to analyze the Marketing Performance Analysis of batik businesses in Pekalongan through Entrepreneurship Orientation, Market Orientation, Product Innovation and E-commerce (Case Study of Batik Traders at the Setono Wholesale Market and IBC Pekalongan) with a total of 158 respondents with a sampling technique using the Stratified technique Random Sampling. The data analysis method used is Multiple Linear Regression using the SPSS ver.22 for Windows program. The results of the tests carried out show that entrepreneurial orientation (X1) has a significant positive effect on marketing performance. Market orientation (X2) has a positive and significant effect on Marketing Performance (Y) with a sig value of 0.007. Product Innovation (X3) has a positive and significant effect on Marketing Performance (Y) with a sig value of 0.000. E-Commerce (X4) has a positive and significant effect on Marketing Performance (Y) with a sig value of 0.042.